MRI Findings in Children with Acute Flaccid Paralysis and Cranial Nerve Dysfunction Occurring during the 2014 Enterovirus D68 Outbreak - Maloney, J.A.; Mirsky, D.M.; Messacar, K.; Dominguez, S.R.; Schreiner, T.; Stence, N.V. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Enterovirus D68 was responsible for widespread outbreaks of respiratory illness throughout the United States in August and September 2014. During this time, several patients presented to our institution with acute flaccid paralysis and cranial nerve dysfunction. The purpose of this report is to describe the unique imaging findings of this neurologic syndrome occurring during an enterovirus D68 outbreak. MATERIALS AND METHODS: Patients meeting a specific case definition of acute flaccid paralysis and/or cranial nerve dysfunction and presenting to our institution during the study period were included. All patients underwent routine MR imaging of the brain and/or spinal cord, including multiplanar T1, T2, and contrast-enhanced T1-weighted imaging. RESULTS: Eleven patients met the inclusion criteria and underwent MR imaging of the brain and/or spinal cord. Nine patients presented with brain stem lesions, most commonly involving the pontine tegmentum, with bilateral facial nerve enhancement in 1 patient. Ten patients had longitudinally extensive spinal cord lesions; those imaged acutely demonstrated involvement of the entire central gray matter, and those imaged subacutely showed lesions restricted to the anterior horn cells. Ventral cauda equina nerve roots enhanced in 4 patients, and ventral cervical nerve roots enhanced in 3, both only in the subacute setting. CONCLUSIONS: Patients presenting with acute flaccid paralysis and/or cranial nerve dysfunction during the recent enterovirus D68 outbreak demonstrate unique imaging findings characterized by brain stem and gray matter spinal cord lesions, similar to the neuroimaging findings described in previous outbreaks of viral myelitis such as enterovirus 71 and poliomyelitis. AFPacute flaccid paralysisEV-D68enterovirus D68EV-71enterovirus 71